Market reaction & motives behind share repurchase : evidence from Japanese companies - Abhay Kumar Sinha (2008)
In this study, we investigated the factors motivating the Japanese companies for share repurchase, the market reaction on announcements of such programmes and the factors related to such repurchase programmes announcement effects.